Study on Structural Relationships among the Factors Affecting Happiness of Adolescent in OECD Countries: Application of QCA Method - Choi, Young-Chool; Jang, Ji-Hyun (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
The purpose of this study is to investigate the causal relationships among the key educational factors that affect adolescent happiness and to propose policy implications for OECD countries to increase their levels of adolescent happiness. The HSBC score of adolescent happiness in OECD countries was chosen as an indicator, and a number of independent variables such as per capita GDP and per capita educational expenditure amount were included in the subject of analysis. For the analysis, the QCA (Qualitative Comparative Analysis) method was used. The use of QCA has been rarely reported in adolescents’ happiness studies, and are likely to be conceptual and paradigmatic challenges to its adoption in some settings. According to the findings, there are three key factors that contribute to adolescents' high levels of happiness in OECD nations: TEPC*GDP*PUPTEA, tee*GDP*PRIVATEXP, and tee*tepc*gdp*privatexp. In other words, while a number of further steps are required to produce a more parsimonious formulation, the solution in this study suggests six configurations and three prime implicants. The first prime implicant is TEPC(high total per capita expenditure on education)*GDP(high per capita gdp)*PUPTEA(high ratio of students to teaching staff). The second implicant is tee(low total expenditure on education)*GDP(high per capita gdp)*PRIVATEXP(high ratio of private source expenditure on education to gdp). Finally, the third implicant is tee(low total expenditure on education)*tepc(low total per capita expenditure on education)*gdp(low per capita gdp)*privatexp(low ratio of private source expenditure on education to gdp). It is crucial to emphasise that the data reported in this research are simply illustrative and should be examined in a broader context.Alternative causal configurations are acceptable for the complexity of adolescents' happiness, rather than being a limitation of QCA.